(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In this subsequent investigation, we expand upon our initial research by delving into the laser engraving and marking of Grade 2 Titanium (Ti Gr 2) using frequencies of 300 kHz and 700 kHz. Building upon our preliminary experiments involving 100 kHz and 500 kHz, we utilized the Rofin PowerLine F 20 Varia fiber laser to mark Grade 2 titanium within a 6x6 matrix, with each square measuring 5x5 mm. Our meticulous adjustments to the laser marking parameters — encompassing speed (100-1100 mm/s), power (8-18 W), and the introduction of new frequencies (300 kHz and 700 kHz) — allowed us to scrutinize their impact on surface roughness and contrast. Employing advanced techniques, including a laser scanning microscope and Adobe Photoshop software, our analysis unveiled explicit connections among contrast, roughness, frequency, scanning speed, and power. These findings not only extend the scope of our previous experiments but also illuminate subtleties specific to the 300 kHz and 700 kHz frequencies. The insights derived from this study furnish crucial information on the optimal laser marking parameters for Grade 2 titanium, thereby augmenting its efficacy and durability across a diverse array of applications. Moreover, this research contributes to the progressive comprehension of color variations in laser-engraved titanium Grade 2, particularly within the 300 kHz and 700 kHz frequency range.